Video education on the knowledge of cosmetics and skin care contact dermatitis: A cross-sectional study - Prasetyo, Muhammad Rizkinanda; Damayanti, Damayanti; Herawati, Lilik; Anggraeni, Sylvia (Journal of General - Procedural Dermatology and Venereology Indonesia, 2025)
Background: Contact dermatitis is an immunologic reaction to irritants, allergens, and is commonly associated with cosmetics and skin-care products. Limited knowledge of this condition increases the risk of improper product use and delays preventive measures. Therefore, education plays a crucial role in fostering a comprehensive understanding of its etiology and prevention. This study aimed to evaluate the effectiveness of a video-based educational intervention in enhancing women’s knowledge regarding contact dermatitis related to cosmetics and skin-care products. Methods: This cross-sectional study collected primary data from 100 female academics aged 17–45 at Airlangga University, Surabaya, East Java, Indonesia. Knowledge of contact dermatitis was assessed using questionnaires administered before and after a video-based educational intervention. Knowledge levels were categorized as low (X < 16/20), medium (16/20 ≤ X ≤ 17/20), and high (X > 17/20). Data were analyzed using the Wilcoxon Signed Rank test (SPSS version 25) and summarized in tables. Results: The medium category (16 ≤ X ≤ 17) was the most common in the pretest (61 respondents) and increased in the post-test (88 respondents). The Wilcoxon Signed Rank Test showed a significant increase in post-test scores following the video-based intervention, with a p-value of 0.008 (p < 0.05). Conclusion: Video-based education significantly improved knowledge regarding contact dermatitis related to cosmetics and skin-care products among women.